Machineries of Oil An Infrastructural History of BP in Iran - Shafiee, Katayoun (Infrastructures, 2018)
Machineries of Oil is an investigation into oil infrastructure in modern society, examining local power struggles over the construction of the global oil industry in a non-western context. This history is crucial for understanding the twentieth-century politics of the Middle East and the peculiar ways in which countries of the Global South have served as irreplaceable laboratories for producing knowledge and know-how on nature and society. This book will come at a time when tensions between the US and Iran, and tensions surrounding the politics of the oil industry in the Middle East in particular, have become unfortunately heightened in the wake of the change in US administration. We feel this book is particularly suited to the Knowledge Unlatched program because our reach to Middle East studies audiences is somewhat limited, and we'd like this book to be available to as many readers as possible, despite limited marketing resources to go beyond our usual channels.